2019
DOI: 10.1002/1878-0261.12547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of circulating tumor DNA mutant allele fraction on prognosis in RAS‐mutant metastatic colorectal cancer

Abstract: Despite major advances in the treatment of metastatic colorectal cancer (mCRC), the survival rate remains very poor. This study aims at exploring the prognostic value of RAS ‐mutant allele fraction (MAF) in plasma in mCRC. Forty‐seven plasma samples from 37 RAS ‐mutated patients with nonresectable metastases were tested for RAS in circulating tumor DNA using BEAMing before first‐ and/or second‐line treatment. RAS MAF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
4
33
1
Order By: Relevance
“…TMB was measured by exome sequencing [ 38 ], counting all coding, somatic base substitutions and indels in the targeted regions, including synonymous alterations. The size of the targeted (coding) genomic region was 1.9 Mb.…”
Section: Methodsmentioning
confidence: 99%
“…TMB was measured by exome sequencing [ 38 ], counting all coding, somatic base substitutions and indels in the targeted regions, including synonymous alterations. The size of the targeted (coding) genomic region was 1.9 Mb.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas a large number of studies have addressed mCRC [15][16][17][18][19][20][21][22][23] only a few have investigated the role of liquid biopsy in early, non-metastatic CRC patients at surgery, e.g. in conditions of extremely low tumor burden [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Many other issues have to be addressed, among them the concordance of data between formalin-fixed, paraffin-embedded (FFPE) tumor tissue determined by PCR standard of care (SoC) analysis and ctDNA. Different studies demonstrated that ctDNA analysis by BEAMing technology or qPCR-based platforms reaches about 90% of concordance when compared with tumor tissue analysis to detect molecular alterations in KRAS, NRAS and BRAF genes (Table 3), [71,75,76]. Concordance between tissue and plasma does not meet 100% due to dynamic changes that occur in CRC disease.…”
Section: Tablementioning
confidence: 99%
“…This dynamic spatial and temporal heterogeneity of CRC could be resolved by repeating genomic profiles at different time points during the course of treatment. Due to the small amount of tumor ctDNA in the blood of patients with mCRC, high sensitive liquid biopsy analysis is always required to avoid false negative results, even if a negative result, in some cases, could be attributed to biological processes that impede the ctDNA release in the blood, the tumor histology (mucinous tumors) and the presence of peritoneal and lung metastases [76]. Of note, analyses of the CRYSTAL phase III study showed that patients with RAS mutant allele fraction (MAF) mutations lower than 5% achieved better outcomes when cetuximab was added to a FOLFIRI based first line treatment [27].…”
Section: Tablementioning
confidence: 99%